Hormone therapy as a management strategy for lung metastasis after 5 years of endometrial cancer: A case report and literature review. Issue 51 (December 2017) - Zhao, Huifang; Yao, Yushuang; Yang, Hongjuan; Ma, Dehua; Chen, Aiping
Abstract: Rationale: Endometrial cancer patients with lung metastases are rare, and more rarely with long-term management of progesterone after recurrence. Patient concerns: Informed consent of the patients and their families. Diagnoses: Endometrial cancer (IVB) (Refer to 2009 FIGO stag of endometrial cancer). Interventions: the patient was treated with Megestrol Acetate Dispersible Tablets (trade name Yilizhi), 160 mg, orally, once daily, without interruption. Outcomes: The patient has been treated with progesterone therapy for stable conditions and her survival time is already roughly a decade (December 2006–October 2016). Lessons: Hormone therapy may as a long-term management for hormone receptor-positive patients with recurrent endometrial cancer.